Depresija in bolečina - Kores-Plesničar, Blanka (Farmacevtski vestnik, 2010)
Depression is one of the leading causes of global disease burden. In addition, depression is frequently associated with troublesomephysical symptoms, such as fatigue, sleep disturbances and appetite changes, and also with painful physical symptoms, like back pain,headache, fibromyalgia and others. Depression and pain have a reciprocal relationship in that one heightens the severity of the other. There remains a clear room for further improvement and change in the approach to elimination of those associated symptoms.
Keywords: bolečina; depresija; fibromialgija